The Sweetpotato BTB-TAZ Protein Gene, IbBT4, Enhances Drought Tolerance in Transgenic Arabidopsis - Zhou, Yuanyuan; Zhai, Hong; He, Shaozhen; Zhu, Hong; Gao, Shaopei; Xing, Shihan; Wei, Zihao; Zhao, Ning; Liu, Qingchang (Frontiers in Plant Science, 2020)
BTB-TAZ (BT)-domain proteins regulate plant development and pathogen defence. However, their roles in resistance to abiotic stresses remain largely unknown. In this study, we found that the sweetpotato BT protein-encoding gene IbBT4 significantly enhanced the drought tolerance of Arabidopsis. IbBT4 expression was induced by PEG6000, H2O2 and brassinosteroids (BRs). The IbBT4-overexpressing Arabidopsis seeds presented higher germination rates and longer roots in comparison with those of WT under 200 mM mannitol stress. Under drought stress the transgenic Arabidopsis plants exhibited significantly increased survival rates and BR and proline contents and decreased water loss rates, MDA content and reactive oxygen species (ROS) levels. IbBT4 overexpression upregulated the BR signalling pathway and proline biosynthesis genes and activated the ROS-scavenging system under drought stress. Yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays revealed that the IbBT4 protein interacts with BR-ENHANCED EXPRESSION 2 (BEE2). Taken together, these results indicate that the IbBT4 gene provides drought tolerance by enhancing both the BR signalling pathway and proline biosynthesis and further activating the ROS-scavenging system in transgenic Arabidopsis.